Frasa nama dalam akhbar Utusan Sarawak - Bolhassan, Nabillah; Salleh, Che Ibrahim (Penerbit Universiti Malaysia Terengganu, 2014)
This article is associated with noun phrases appearing in Utusan Sarawak. Newspaper Utusan Sarawak is to be used as the primary source for news by readers, especially in Sarawak. The objective of this study was to identify and analyze the noun phrase in Utusan Sarawak weekly edition dated July 22, 2012, Sunday, which involves the entire space available in the newspaper. This study uses textual analysis methods. The theory used is generative transformation. Through this study, researchers found that there are several types of noun phrases that are frequently used by the editors of Utusan Sarawak as gender noun phrase, noun phrase classification, ancestry noun phrase, noun phrase performer, a noun phrase, noun phrase tools, muasal noun phrase, noun phrase groups and more. The results showed that the study has implications for students to increase understanding of the noun phrase. Next could help one master the Malay language better.